KNOWLEDGE ON SALIVARY BIOMARKERS IN ORAL CANCER DETECTION AMONG DENTAL STUDENTS - M, Indumathi; Santhanam, Archana; S, Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Background: Oral cancers are the sixth most frequent cancer with a high mortality rate. Oral squamous cell carcinoma accounts for more than 90% of all oral cancers. The use of saliva for early cancer detection in the search for new clinical markers is a promising approach because of its non-invasive sampling methods.Saliva’s direct contact with oral cancer lesions makes it a more specific and potentially sensitive screening tool. The identification of potential salivary signatures for early, noninvasive detection of OSCC leads to early detection, a better outcome, and survival. More than 100 biomarkers have been identified at differential levels in the saliva of patients with OSCC. Most cases of OSCC are detected in advanced stages; thus, a reliable early-stage diagnostic marker is needed. Aim: The aim of the present study is to assess the knowledge and awareness of salivary biomarkers in oral cancer detection among undergraduate dental students. Materials and methods: A descriptive cross-sectional survey was conducted among undergraduate dental college students aged 18–25 years from March to April 2020 to assess their knowledge and awareness of salivary biomarkers in oral cancer detection. A total of 280 participants were involved in the study. A self-administered questionnaire of closed-ended questions was prepared, and it was distributed among undergraduate dental college students through the online survey “Google Forms." The responses were collected, tabulated in an Excel sheet, and analysed using SPSS software. A chi square test was used to analyze the level of education of students and their knowledge on salivary biomarkers in oral cancer detection with a statistical significance of P < 0.05. Results: The majority of the participants (92.1%) were aware that oral squamous cell carcinoma accounts for more than 90% of all oral cancers. 79.6% of the participants were aware that salivary biomarkers should be used to discriminate between physiological and pathological conditions. Conclusion: The majority of the second-year undergraduate students had very good knowledge on salivary biomarkers for oral cancer detection.